Antiurease screening of alkyl chain-linked thiourea derivatives: in vitro biological activities, molecular docking, and dynamic simulations studies. Issue 10 (23rd February 2022) - Yaqoob, Sana; Hameed, Abdul; Ahmed, Mahmood; Imran, Muhammad; Qadir, Muhammad Abdul; Ramzan, Mahwish; Yousaf, Numan; Iqbal, Jamshed; Muddassar, Muhammad
Abstract : Urease has become an important therapeutic target because it stimulates the pathogenesis of many human health conditions, such as pyelonephritis, the development of urolithiasis, hepatic encephalopathy, peptic ulcers, gastritis and gastric cancer. Abstract : Urease has become an important therapeutic target because it stimulates the pathogenesis of many human health conditions, such as pyelonephritis, the development of urolithiasis, hepatic encephalopathy, peptic ulcers, gastritis and gastric cancer. A series of alkyl chain-linked thiourea derivatives were synthesized to screen for urease inhibition activity. Structure elucidation of these compounds was done by spectral studies, such as IR, 1 H NMR and 13 C NMR, and MS analysis. In vitro urease enzyme inhibition assay revealed that compound 3c was the most potent thiourea derivative among the series with IC50 values of 10.65 ± 0.45 μM, while compound 3g also exhibited good activity with an IC50 value of 15.19 ± 0.58 μM compared to standard thiourea with an IC50 value of 15.51 ± 0.11 μM. The other compounds in the series possessed moderate to weak urease inhibition activity with IC50 values ranging from 20.16 ± 0.48 to 60.11 ± 0.78 μM. The most potent compounds 3c and 3g were docked to jack bean urease (PDB ID: ; 4H9M ) to evaluate their binding affinities and to find the plausible binding poses. The docked complexes were refined through 100 ns-long MD simulations. The simulation results revealed that the average RMSD of 3c was less than that of the 3g compound. Furthermore, the radius of gyration plots for both complexes showed that 3c and 3g docking predicted binding modes did not induce any conformational change in the urease structure.